Bhagawat Geeta an Epitome of Phenomenal Life Experience: A Review - Bhattarai, Bedhraj (New Journey, 2024)
The Bhagawat Geeta, a sacred Hindu scripture, has been revered for centuries as a profound source of wisdom and guidance on living a meaningful and fulfilling life. According to Sarabu (2019) the Bhagavad Gita shows the way to lead a successful life and at the end to get rid of from this materialistic world by planning their lives to achieve salvation. In this review, I delve into the essence of the Bhagawat Geeta and explore how it encapsulates the essence of living a phenomenal life. In this paper, I would examine its teachings and philosophical insights towards the life. While exploring and examining its core crux, it aims to shed light on the timeless relevance and practicality of this ancient text of the Hindu scripture.